2017
DOI: 10.24912/jm.v20i1.62
|View full text |Cite
|
Sign up to set email alerts
|

Commitment Sebagai Variabel Mediasi Pengaruh Trust Terhadap Repurchase Intention Pada Restoran Waralaba Lokal

Abstract: Abstract:Franchising is a form of retail businesses, especially those of growing and promising restaurants. Competition is becoming more tightly multiplied by the entry of foreign franchisors. Customer loyalty is the key to win the competition. The purpose of this study is to analyze the trust, affective commitment, continuance commitment towards repurchase intention. Respondents as the sample of this study were 200 respondents who visited local franchise restaurants, chosen by using Purposive Sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…Theoretically, the findings of this research support the results of the previous study [8], [22], [26]. We also found that trust was positively effecting to commitment, which is consistent with the findings of prior scholars [21], [24], [27]. The data analysis results also revealed that Satisfaction was positively related to revisiting intention, which matches the finding of previous researchers [19], [30]- [32].…”
Section: Table 4 Hypotheses Testing Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Theoretically, the findings of this research support the results of the previous study [8], [22], [26]. We also found that trust was positively effecting to commitment, which is consistent with the findings of prior scholars [21], [24], [27]. The data analysis results also revealed that Satisfaction was positively related to revisiting intention, which matches the finding of previous researchers [19], [30]- [32].…”
Section: Table 4 Hypotheses Testing Resultssupporting
confidence: 91%
“…Mosavi & Ghaedi [21]found that trust has a positive influence on customer loyalty, repurchase intention, and customer commitment in Iran. It is also supported in the local franchise restaurants industry [27] and the hospitality industry in Taiwan [24]. Based on the discussion above, so we developed hypotheses as below:…”
Section: Trustmentioning
confidence: 99%
“…(Haryono et al, 2015;Prameka et al, 2016;Zeglat et al, 2016). Penelitian ini mengkonfirmasi penelitian Parasuraman et al (Chou & Chen, 2018;Ferro et al, 2016;Li & Chang, 2016;Mlaker Kač et al, 2015;Riorini, 2016…”
Section: 678unclassified